Performance study of a 248 GHz voltage controlled hetero-integrated source in InP-on-BiCMOS technology. Issue 2 (13th November 2015) - Hossain, Maruf; Ostermay, Ina; Weimann, Nils G.; Schmueckle, Franz Josef; Borngraeber, Johannes; Meliani, Chafik; Lisker, Marco; Tillack, Bernd; Krueger, Olaf; Krozer, Viktor; Heinrich, Wolfgang
Abstract : This paper presents the performance study of a 248 GHz voltage-controlled hetero-integrated signal source using indium phosphide (InP)-on-bipolar complementary metal-oxide-semiconductor (BiCMOS) technology. The source consists of a voltage controlled oscillator (VCO) in 0.25 µm BiCMOS technology and a frequency multiplier in 0.8 µm transferred-substrate InP-heterojunction bipolar transistor technology, which is integrated on top of the BiCMOS monolithic microwave integrated circuit in a wafer-level based benzocyclobutene bonding process. The vertical transitions from BiCMOS to InP in this process exhibit broadband properties with insertion losses below 0.5 dB up to 325 GHz. The VCO operates at 82.7 GHz with an output power of 6 dBm and the combined circuit delivers −9 dBm at 248 GHz with 1.22% tuning range. The phase noise of the combined circuit is −85 dBc/Hz at 1 MHz offset. The measured output return loss of the hetero-integrated source is >10 dB within a broad frequency range. This result shows the potential of the hetero integrated process for THz frequencies.